THE EFFECTIVENESS OF THE BPJS HEALTH PROGRAM IN ADDRESSING HEALTH PROBLEMS IN INDONESIA - Riza, Mohamad (Proceeding International Seminar of Islamic Studies, 2024)
Social Security Administering Body (BPJS) Law Number 24 of 2011 concerning Social Security Administering Body (BPJS) established two Social Security administering bodies, namely BPJS Health and BPJS Employment. The Social Security Administering Agency (BPJS) for health is the result of the transformation of access, Jamkesda or Jamkesmas. BPJS health is divided into three categories of membership, namely BPJS Mandiri or Individual, BPJS for Wage Recipient Workers (PPU), and BPJS Contribution Assistance Participants (PBI). The BPJS health program in Indonesia as a whole can now be said to be running, with the existence of rules or a legal system that regulates this, making it legal, fair and beneficial for the Indonesian people. BPJS health in Indonesia can be said to be effective in maintaining the health of the Indonesian people, who basically have rights that the State must fulfill regarding health.